2009
DOI: 10.1002/hyp.7312
|View full text |Cite
|
Sign up to set email alerts
|

Low and high flow analyses and wavelet application for characterization of the Blue Nile River system

Abstract: Abstract:The low and high flow characteristic of the Blue Nile River (BNR) basin is presented. The study discusses low and high flow, flow duration curve (FDC) and trend analysis of the BNR and its major tributaries. Different probability density functions were fitted to better describe the low and high flows of the BNR and major tributaries in the basin. Wavelet analysis was used in understanding the variance and frequency-time localization and detection of dominant oscillations in rainfall and flow. FDCs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 15 publications
0
26
1
Order By: Relevance
“…Generally, for the BNR basin, high streamflows are concentrated between July and October, lagging the start of the Kiremt season by one month, while low streamflows occur between February and April. Melesse et al (2009) observe greater in magnitude and more sustained streamflows along the main stem of the BNR at Kessie and Bahirdar stations than in the tributary rivers, which is not unexpected given the aggregation of streamflows across sub basins of varying characteristics and rainfall-runoff properties. Similarly, based on twelve sub-basins in the BNR basin, Gebrehiwot et al (2014) illustrate the stark differences when comparing mean annual high streamflows, ranging from 525 mm/year to 26 mm/year, expressed as equivalent depth of water over the Beresa and Muger sub-basins, respectively.…”
Section: Characteristics and Distributions Of Precipitation And Streamentioning
confidence: 52%
See 2 more Smart Citations
“…Generally, for the BNR basin, high streamflows are concentrated between July and October, lagging the start of the Kiremt season by one month, while low streamflows occur between February and April. Melesse et al (2009) observe greater in magnitude and more sustained streamflows along the main stem of the BNR at Kessie and Bahirdar stations than in the tributary rivers, which is not unexpected given the aggregation of streamflows across sub basins of varying characteristics and rainfall-runoff properties. Similarly, based on twelve sub-basins in the BNR basin, Gebrehiwot et al (2014) illustrate the stark differences when comparing mean annual high streamflows, ranging from 525 mm/year to 26 mm/year, expressed as equivalent depth of water over the Beresa and Muger sub-basins, respectively.…”
Section: Characteristics and Distributions Of Precipitation And Streamentioning
confidence: 52%
“…In contrast, when stations located in the Ethiopian part of the BNR basin are analyzed, the probability distribution best explaining high and low streamflows varies by river. Melesse et al (2009) examine two stations on the main stem (Kessie and Bahirdar) and five stations on the major tributaries (Gilgel Abay, Chemoga, Megech, Gumera and Ribb) of the basin. Their results suggest that high and low streamflows are best fit with diverse distributions, namely the General Pareto, Fréchet, Log normal, Log logistics, and Weibull distributions.…”
Section: Characteristics and Distributions Of Precipitation And Streamentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing need of meteorological forcing data with high precision and temporal-spatial resolution for driving hydrological models to provide reliable model simulations to support water and land management practices. Recent studies show that the quality of meteorological data has been a major uncertainty source for determining model performance (Collick et al, 2009, Kim et al, 2008a, Kim et al, 2008b, Muluneh et al, 2009, Melesse et al, 2010. Therefore, improving data accuracy is important for effectively reducing model uncertainty (Neitsch et al, 2009, Zhang et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Considering precipitation, most studies e.g., (Bewket and Sterk, 2005;Cheung et al, 2008;Conway, 2000;Gebremicael et al, 2013;Melesse et al, 2009;Rientjes et al, 2011;Seleshi and Zanke, 2004;Teferi et al, 2013;Tekleab et al, 2014;Tesemma et al, 2010) report no significant trend in annual and seasonal precipitation totals within the Lake Tana sub-basin, where there are relatively better hydro-meteorological data, while 20 Mengistu et al (2014) reported statistically non-significant increasing trends at annual and seasonal except Belg season.…”
mentioning
confidence: 99%